2017
DOI: 10.1093/pcp/pcx181
|View full text |Cite|
|
Sign up to set email alerts
|

Salicylic Acid and Jasmonic Acid Pathways are Activated in Spatially Different Domains Around the Infection Site During Effector-Triggered Immunity in Arabidopsis thaliana

Abstract: The innate immune response is, in the first place, elicited at the site of infection. Thus, the host response can be different among the infected cells and the cells surrounding them. Effector-triggered immunity (ETI), a form of innate immunity in plants, is triggered by specific recognition between pathogen effectors and their corresponding plant cytosolic immune receptors, resulting in rapid localized cell death known as hypersensitive response (HR). HR cell death is usually limited to a few cells at the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(128 citation statements)
references
References 36 publications
12
115
0
1
Order By: Relevance
“…As a plant hormone, SA plays a significant role in fighting disease (Shirasu et al 1997; Betsuyaku et al 2017). With increasing concentrations of SA, plants increase resistance to pathogens by triggering defense gene expression and H 2 O 2 accumulation (Shirasu et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As a plant hormone, SA plays a significant role in fighting disease (Shirasu et al 1997; Betsuyaku et al 2017). With increasing concentrations of SA, plants increase resistance to pathogens by triggering defense gene expression and H 2 O 2 accumulation (Shirasu et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…During ETI, a concentration gradient of SA is formed around the pathogen infection site that eventually undergoes HR cell death . Intravital time‐lapse imaging of the promoter activities of the SA maker gene PR1 and the JA marker gene VSP1 during Pto AvrRpt2‐triggered ETI showed that JA signaling is activated in a spatial domain surrounding the HR area at an early stage, which is followed by activation of SA signaling in the region between the HR‐ and JA‐active domains . This temporally dynamic and spatially separated activation of JA and SA signaling during ETI could be interpreted as a plant strategy to locally confine the SA‐active cells via JA‐SA antagonism and to create JA‐active cells for preventing secondary infection by necrotrophic pathogens that are sensitive to JA‐mediated immunity .…”
Section: Immune Signaling Networkmentioning
confidence: 94%
“…However, it was shown that prior ETI activation in one half of a leaf has no effect on promoting the growth of the necrotrophic fungus Alternaria brassicicola in the other leaf half . Furthermore, ETI‐associated cell death and defense responses are tightly regulated in a spatiotemporal manner . Therefore, it may be possible that spatiotemporal regulation of ETI responses including cell death provides certain tolerance against exploitation by necrotrophic pathogens.…”
Section: Immune Receptor Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [145] showed that SA promotes the synthesis of JA and the activation of its signaling during ETI. However, a recent study by Betsuyaku et al [146] showed that SA and JA act antagonistically during ETI on a narrow spatial scale. So far, spatial information on JA responses in non-flowering plants is only available for conifers, where MeJA treatment results in cell type-specific PAL activation [17].…”
Section: Evolution Of Phytohormone Defense Networkmentioning
confidence: 99%